Seedless jamun fruits - Singh, A K; Bajpai, Anuj; Shankar, H. Ravi (Indian Horticulture, 2019)
Jamun has emerged as nutitive and very rich source of natureceuticals. The seed is a problem in making its commercial products. But scientists of the CISH, Lucknow, have developed a seedless variety which will be a boon for our jamun eaters and to industries as well.